The Effectiveness of Outline Technique on Students' Writing Skills in Coherent Paragraphs - Rizqiyani, Nabila (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2023)
Writing is the activity of expressing and communicating ideas in words. People write letters, text his messages, e-mails to communicate and may also express their feelings by writing diaries. By writing, people create and express their ideas in an organized process. The more they write, the better their thinking skill will be. This research is quantitative research using quasi-experimental design (post- test only). Re- searchers conducted research on students at MAN 02 Jember. There are two research variables, the independent variable is an outline technique, the dependent variable is writing skills. The researcher took two classes as samples, X Agama 1 consist of 25 students (experimental group) and X Agama 2 consist of 25 students (control group). The research instrument used in this method is essay questions. Based on the results, the average value of the experimental class for the post- test was 82.80. The average value of the experimental group is higher than the average value of the control group. The sig- nificance value based on the analysis on the test is 0.000 <0.05. The alternative hy- pothesis (Ha) is accepted because there is a significant difference in writing skill between students who are taught with an outline technique and students who are taught with teacher conventional method. From the results, can be concluded that there is a significant effect of the Outline Technique on Students' Writing Skills in Coherent Paragraphs at MAN 02 Jember in the 2022/2023 academic year.